2021
DOI: 10.1002/cncr.33830
|View full text |Cite
|
Sign up to set email alerts
|

A novel combined resilience and advance care planning intervention for adolescents and young adults with advanced cancer: A feasibility and acceptability cohort study

Abstract: Background Few evidence‐based psychosocial programs have been tested among adolescents and young adults (AYAs) with advanced cancer (AC), and early advance care planning (ACP) in this population is rare. The authors aimed to determine the feasibility and acceptability of 1) delivering an established resilience‐coaching program, and 2) integrating ACP into that program, among AYAs with AC. Methods Eligible AYAs were 12 to 24 years old, diagnosed with advanced cancer (recurrent/refractory disease or a diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 34 publications
(52 reference statements)
1
31
0
Order By: Relevance
“…Prioritizing appropriate communication training (EPEC, 2019; The Conversation Project, 2020; Vital Talk, 2021), and incorporating ACP discussions into routine care alongside the use of a structured ACP guide, may greatly improve patient-centered EoL care. A recent study found integrating ACP using pages of VMC into an existing resilience-coaching intervention for AYAs with advance cancer both feasible and acceptable (Fladeboe et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Prioritizing appropriate communication training (EPEC, 2019; The Conversation Project, 2020; Vital Talk, 2021), and incorporating ACP discussions into routine care alongside the use of a structured ACP guide, may greatly improve patient-centered EoL care. A recent study found integrating ACP using pages of VMC into an existing resilience-coaching intervention for AYAs with advance cancer both feasible and acceptable (Fladeboe et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…conducted directed content analysis with Dedoose qualitative analysis software, version 7.0.23 (SocioCultural Research Consultants LLC) using an a priori codebook based on questions from the interview guide and informed by previous PRISM trials. 39 Once the codebook was finalized, the same coders sequentially coded each transcript into code categories. Consensus meetings refined codes and resolved discrepancies.…”
Section: Methodsmentioning
confidence: 99%
“…Based on other studies assessing the feasibility of an intervention for children and their parents, the following feasibility criteria were pre-defined: Eligibility: ≥70% of patients are eligible for the intervention [ 48 , 49 ]. Recruitment: ≥50% of patients approached are recruited [ 50 , 51 , 52 ]. Retention: ≥75% of participants are retained in the intervention after one year [ 49 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“… Retention: ≥75% of participants are retained in the intervention after one year [ 49 , 51 ]. Attendance: ≥70% of participants attend the planned visits (initial evaluation and follow-up visits) [ 50 , 51 ]. Completion of study measures: acceptable if ≥70% of participants complete the measures and feasible if ≥85% of participants do so [ 48 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation